SISTEM MANAJEMEN WAKAF DI JORDANIA - Mahsun Mahsun (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
The wakaf management system in Jordan has been running fairly orderly and professional with the full support of both the kingdom and the government, so that the wealth of waqf can function and provide great benefits to the Jordanian people, such as welfare for the poor, orphans, some schools, scholarships students and others. The development of wakaf wealth management in Jordan is also in the form of an innovative utilization of wakaf's property in order to become a continuously flowing fund (investment fund). The wakaf family law system which is a compromise and a blend of Islamic and Western law is a factor that strongly supports the rapid development of progress in the management of waqf in Jordan.